2019
DOI: 10.26503/todigra.v4i3.103
|View full text |Cite
|
Sign up to set email alerts
|

Free-to-Play or Pay-to-Win? Casual, Hardcore, and Hearthstone

Abstract: “Casual” and “hardcore” are commonly used descriptive terms for games and gamers. While critics have discussed these terms with regards to game design and culture, “free-to-play” games like Blizzard’s Hearthstone add a monetary dimension to such considerations. Players can play such games for free, but success at them often entails purchasing in-game content. These games are sometimes instead derisively referred to as “pay-to-win:” players who spend money win more often. Free-to-play games suggest that casual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These games employ blockchain technology to foster a secure and transparent environment where players can buy, sell, and trade their in-game assets akin to real-world market transactions. The gaming industry has evolved from "play-to-win" games, which necessitate skill enhancement to defeat opponents, to the "pay-to-win" model, and now to the "play-to-earn" games that facilitate earning money [1,2]. Existing video games provide opportunities for players to make money by selling in-game items, but these differ from PTE games due to the utilization of NFTs.…”
Section: Introductionmentioning
confidence: 99%
“…These games employ blockchain technology to foster a secure and transparent environment where players can buy, sell, and trade their in-game assets akin to real-world market transactions. The gaming industry has evolved from "play-to-win" games, which necessitate skill enhancement to defeat opponents, to the "pay-to-win" model, and now to the "play-to-earn" games that facilitate earning money [1,2]. Existing video games provide opportunities for players to make money by selling in-game items, but these differ from PTE games due to the utilization of NFTs.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, academics and mental health workers have expressed concern about the detrimental effects of the incorporation of microtransactions in modern video games. These ‘predatory monetization schemes’ [ 13 ] not only create potential financial damages [ 14 ], but also increase the risk of developing Internet gaming disorder (IGD) [ 15 , 16 ] since F2P games encourage casual players to become more hardcore gamers [ 17 ]. Dreier et al [ 18 ] found that 5.2% of their sample of F2P gamers met criteria for IGD.…”
Section: Introductionmentioning
confidence: 99%